2013
DOI: 10.1002/polb.23330
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fullerene photodimerization on the PCBM crystallization in polymer: Fullerene bulk heterojunctions under thermal stress

Abstract: For an increased lifetime of polymer:fullerene bulk heterojunction (BHJ) solar cells, an understanding of the chemical and morphological degradation phenomena taking place under operational conditions is crucial. Phase separation between polymer and fullerene induced by thermal stress has been pointed out as a major issue to overcome. While often the effect of thermal stress on the morphology of polymer:fullerene BHJ is investigated in the darkness, here we observe that light exposure slows down fullerene crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 27 publications
(44 reference statements)
1
61
0
2
Order By: Relevance
“…Fullerenes tend to diffuse through layers to form large mm-scale crystals or to accumulate at active layer-electrode interfaces, 12 both occurring notably when heated above the glass transition temperature and potentially leading to reductions in device efficiencies. 11,13,14 While photo-induced reactions between PCBM molecules may lead to morphological stability, 15,16 they can also give rise to dimers that act as charge traps and reduce short circuit current ( J sc ) values. 17 PCBM is also difficult to cast as a thin film, resulting in rough surfaces of large aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fullerenes tend to diffuse through layers to form large mm-scale crystals or to accumulate at active layer-electrode interfaces, 12 both occurring notably when heated above the glass transition temperature and potentially leading to reductions in device efficiencies. 11,13,14 While photo-induced reactions between PCBM molecules may lead to morphological stability, 15,16 they can also give rise to dimers that act as charge traps and reduce short circuit current ( J sc ) values. 17 PCBM is also difficult to cast as a thin film, resulting in rough surfaces of large aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works in the literature have demonstrated that the rate of fullerene aggregation is strongly dependent on its diffusivity and miscibility as well as the extent of photo-induced dimerisation between fullerenes within a polymer matrix. 14,16,17,50,51 These properties are heavily influenced by polymer backbone and side-chain structure and the amorphous/ void space fractions of the thin films through which small molecules may more easily traverse. 17,52 Therefore, it should follow that acceptor migration and aggregation within polymers containing distinctly different backbones and side-chains, and featuring differences in crystallinity and glass transition temperatures should exhibit dissimilar behavior with respect to morphological development.…”
mentioning
confidence: 99%
“…1 Despite considerable improvements in the PCE of these devices, the long term stability is still sub-optimal for successful commercialization. [7][8][9][10] Several strategies have been employed to improve morphological stability in the active layer of BHJ solar cells. The size of the domains should be small enough to provide large enough interfacial area for efficient exciton dissociation and the separation between them should be short enough to prevent recombination.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 2a, phase-separated fullerene-rich clusters as shown in the dark areas and polymer-rich part in the bright areas were observed. [13,14] When the amount of TCB in polymer blend film was increased to10 and 20 mg ml -1 , the domains of PCDTBT-rich and PC 71 BM-rich (bright and dark areas respectively) were observed as an uniformed phase separation and smaller size than those of the film without TCB as indicated in Figure 2b and 2c, respectively. When TCB concentration increased more than 20 mg ml -1 , the domain size of the PCDTBT-rich part and the PC 71 BM-rich one gradually increased as displayed in Figure 2d to Figure 2f.…”
Section: Methodsmentioning
confidence: 96%